Effect of rooting media on germination and seedling growth of nutmeg (Myristica fragrans Houtt.) - P C Haldavnekar, V S Pande, R G Khandekar, L K Dashora, G D Joshi, P M Haldankar, U A Gadre, M C Jain (Journal of Spices and Aromatic Crops, 2006)
Experiments conducted on germination of nutmeg (Myristica fragrans) seeds at Dapoli(Maharashtra) indicated that there were significant differences in germination of seeds sownin different media. The mean germination was significantly higher in seeds sown in ricebran (82.3%) which was on par with sand (82.0%) and sand + rice bran (81.7%). Thesemedia also recorded significantly lesser time for first emergence namely, 27.17 days (ricebran), 28.10 days (sand + rice bran) and 28.50 days (sand), respectively. The time taken forfinal emergence was also significantly lower in seeds sown in rice bran (80.83 days), sand +rice bran (81.60 days) and sand (82.17 days), respectively. The vegetative growth of seed-lings namely, shoot length, shoot diameter, number of leaves and leaf area were also signifi-cantly higher in these media namely, rice bran, sand + rice bran and sand at 30, 90 and 180days after germination.